2016
DOI: 10.1016/j.fertnstert.2015.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Subfertility increases risk of testicular cancer: evidence from population-based semen samples

Abstract: Objective To further understand the association between semen quality and cancer risk using well-defined semen parameters. Design Retrospective cohort study. Setting Subfertility Heath and Assisted Reproduction (SHARE) study in Utah from 1994 to 2011. Patients 20,433 men from that underwent semen analysis (SA) and a sample of 20,433 fertile controls matched on age and birth year Interventions none. Main Outcome Measures Risk of all cancers, as well as site-specific results for prostate, testicular, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 19 publications
0
85
0
1
Order By: Relevance
“…Similar to our prior work, we found this elevated cancer risk in oligozoospermic but not azoospermic men and their family members. 17 A possible explanation for this is that the aberrant stem cells found in both these groups could theoretically represent a somatic stem cell dysregulation leading to cancer. However, the genetics underlying this are so disordered in the azoospermic group that they are nonfunctional and not associated with familial cancer risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our prior work, we found this elevated cancer risk in oligozoospermic but not azoospermic men and their family members. 17 A possible explanation for this is that the aberrant stem cells found in both these groups could theoretically represent a somatic stem cell dysregulation leading to cancer. However, the genetics underlying this are so disordered in the azoospermic group that they are nonfunctional and not associated with familial cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Details regarding the subcategorization of semen parameters in this data set were previously published. 17 …”
Section: Methodsmentioning
confidence: 99%
“…In cases where men had more than one semen sample (17% of patients), the average concentration, count, and motility across measures was used. Figure 2 shows the definitions for each semen parameter (Hanson et al, 2016). In general, each parameter is either divided into azoospermic, oligozoospermic, normozoospermic and hyperzoospermic categories or is divided into quartiles.…”
Section: Semen Parametersmentioning
confidence: 99%
“…Cohort studies with information on prospectively-obtained semen parameters have consistently found an association between impaired semen quality and risk of testicular cancer [1419]. When the lag-time between semen analysis and cancer diagnosis was considered, the risk of testicular cancer seemed to be especially increased in the same year or in the year after semen analysis [5, 15], although it was also evident for longer lag times, indicating that the association was affected by reverse causation and/or detection bias to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…sperm count and motility, serum Inhibin B, FSH, and testosterone) are less consistent and more difficult to investigate than the number of children fathered, due to problems of reverse causation, measurement errors, and recall and detection bias. Cohort studies of men evaluated for infertility [1419] have found an increased risk of testicular cancer among those with abnormal semen analyses or male-factor infertility. These studies have the strength of prospective measurements of fertility, often using semen analysis, but they may be affected by other sources of bias, including confounding by cryptorchidism, and detection bias.…”
Section: Introductionmentioning
confidence: 99%